First record of whitebarred goby Amblygobius phalaena (Valenciennes, 1837) from Indian waters - Daniel, N.; Kumar, A. Pavan-; Shankar, Kiruba; Raj, Praveen; Pandian, A. Kathirvel; Roy, S. Dam; Chaudhari, A. (Indian Journal of Fisheries, 2018)
Gobiid fishes are one of the dominant and cryptic taxa in tropical coral reefs. Andaman and Nicobar Islands of India consist of fringing and barrier reefs which harbour huge fish diversity. Due to morphological ambiguity and cryptic life styles, identification and delimitation of gobiids is difficult. In the present study, we report the occurrence of Amblygobius phalaena (Valenciennes, 1837) for the first time in the Indian waters using morphology and DNA barcoding approach. A. phalaena from Indian waters showed divergence values within the range of 0.00 to 0.047 with the reported conspecific individuals.